Characterization of the complete chloroplast genome sequence of Sarcandra glabra (Chloranthales). Issue 1 (2nd January 2020) - Wang, Wei; Zou, Peishan; Liu, Guofeng; Dai, Seping
Abstract: Sarcandra glabra is a perennial evergreen subshrub, with high ornamental and medicinal value. Using the Illumina high-throughput sequencing data, its chloroplast genome is well assembled and characterized. The complete chloroplast genome is 158, 872 bp in length with a typical quadripartite structure: a pair of inverted repeats (IRs) of 26, 122 bp for each, an 88, 182 bp large single-copy (LSC) region and an 18, 445 bp small single-copy (SSC) region. It was composed of 128 genes and they were identified 84 coding genes, 8 rRNA genes, 36 tRNA genes. Phylogenetic analysis confirmed that the position of S. glabra lay within the order Chloranthales instead of Piperales simply according to classical morphological taxonomy.